SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK DI PT RADIANT ASIA PACIFIC DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Muhammad Awalurijal Apriza; Naely Farkhatin (CV. ALIM'SPUBLISHING, 2023)
The purpose of this research is to develop a decision support system for selecting the best existing employees in order to facilitate data collection and the process of selecting the best employees. The research methodology used in the data processing system is the literature study method, namely data collection which is carried out by taking data from various books in the library, journals and other books that can be used as a basis for analyzing problems that can be discussed in research, as well as field study methods. namely by making direct observations such as interviews and observations. The problem solving algorithm used is the Analytical Hierarchy Process. The result of this research is that there is an application tool made with the Java programming language and storing data using a database from MySQL so that the process of data collection and selection of the best employees at PT Radiant Asia Pacific becomes more effective, efficient and practical.